Bulgaria : 2015 Article IV Consultation-Staff Report; Press Release; and Statement by the Executive Director for Bulgaria. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that Bulgaria achieved modest economic growth in 2014, which is expected to continue in 2015, albeit at a lower rate. Consumer prices declined by an average 1.6 percent in 2014, among the sharpest contractions in the European Union, but are projected to turn positive late in the year. The banking system has shown substantial resilience to the damage to confidence resulting from the bank failure. The budget targets a 3 percent of GDP deficit in 2015, and a further 0.5 percentage point reduction per year in coming years. Measures to improve the composition and quality of expenditure and mitigate contingent liabilities arising from state-owned enterprises remain the key.